Inhibition of radiographic progression with combination etanercept and methotrexate in patients with moderately active rheumatoid arthritis previously treated with monotherapy. Issue 7 (21st August 2008) - van der Heijde, D; Burmester, G; Melo-Gomes, J; Codreanu, C; Mola, E Martin; Pedersen, R; Robertson, D; Chang, D; Koenig, A; Freundlich, B; ,
Abstract : Objective: To determine the effect of changing from etanercept or methotrexate monotherapy to etanercept plus methotrexate combination therapy on radiographic progression in rheumatoid arthritis (RA) patients. Methods: Patients enrolled in this 1-year open-label study previously completed a 3-year blinded study in which they received methotrexate or etanercept monotherapy or the combination of both. All patients received the combination of etanercept 25 mg subcutaneously twice weekly plus oral methotrexate up to 20 mg/week. The primary radiographic endpoint was a change in modified total Sharp score (TSS), as assessed by blinded readers. Results: At baseline, patients previously receiving methotrexate monotherapy (etanercept-added, n  =  52) or etanercept monotherapy (methotrexate-added, n  =  68) had moderate disease activity levels (mean disease activity score (DAS) of 2.6 and 2.5, respectively), whereas patients previously receiving combination therapy (n  =  90) had a low disease activity level (mean DAS of 2.0). The addition of etanercept to methotrexate monotherapy resulted in a significant reduction in radiographic progression (p<0.05). Mean TSS changes in the previous year versus the current year were +1.79 versus +0.25 for the etanercept-added group (p<0.05); +0.51 versus −0.18 for the methotrexate-added group (NS) and +0.42 versus +0.24 for the combination group (NS). Conclusion: In these RA patients with on average moderate disease activity despite previous methotrexate monotherapy, combination treatment with etanercept and methotrexate inhibited radiographic progression and improved radiographic outcomes. These data, in conjunction with the previously published clinical data, support the use of combination therapy in RA patients with moderate disease activity.